Radical feminism today - Thompson, Denise (SAGE, 2001)
Radical Feminism Today offers a timely and engaging account of exactly what feminism is, and what it is not. Denise Thompson questions much of what has come to be taken for granted as f̀eminism' and points to the limitations of implicitly defining feminism in terms of ẁomen', g̀ender', d̀ifference' or r̀ace/gender/class'. She challenges some of the most widely accepted ideas about feminism and in doing so opens up a number of hitheto closed debates, allowing for the possibility of moving those debates further.